Language Learning form an Intercultural Perspective: Exploring Afro Culture - Fernández Benavides, Alejandro; Cruz Mosquera, Andrea María; Castrillón Valderrama, Catalina (Colombian Applied Linguistics Journal, 2024)
Due to the highly globalized nature of communication and the increasing acknowledgement of the role of one’s social context in language learning, the intercultural dimension has increasingly been included in the EFL agenda. Nevertheless, the exploration of one’s own culture and local context still requires closer attention. Hence, this qualitative action-research study examines how ninth graders conceptualized their own culture and reflected upon their local cultural symbols and practices after the implementation of a pedagogic proposal based on an intercultural view of language teaching. Data were collected through surveys and class workshops. Thematic analysis was applied. Findings suggest that the students identified with Afro- Colombian culture and its symbolic representations. Furthermore, they discussed the meaning of Afro Culture and its diverse components. Similarly, some activities such as poster design, dancing performances, and oral presentations stood out as amongst the most useful to promote intercultural skills.